Amelioration of Androgenetic Alopecia by Algal Oligosaccharides Prepared by Deep-Sea Bacterium Biodegradation - Jin, Min; Chen, Yu-Lei; He, Xiongfei; Hou, Yanping; Chan, Zhuhua; Zeng, Runying (Frontiers in Microbiology, 2020)
Androgenetic alopecia (AGA) is a dihydrotestosterone (DHT)-mediated hair loss disorder characterized by shortened anagen hair cycle. Oligosaccharides derived from seaweeds possess diverse biological functions. However, little is known about their effects on AGA. In this study, algal oligosaccharide (AOS) was characterized for its mitigation effects on key features involved in AGA pathogenesis, such as DHT- mediated cellular signaling and shortened anagen hair cycle. AOS with varying degrees of polymerization (DP), namely, AOS (DP2), AOS (DP4-6) and AOS (DP8-12), were prepared by agar biodegradation with Flammeovirga pacifica WPAGA1, an agarolytic bacterium isolated from deep sea sediments. In vitro results showed that AOS with varying DPs significantly ameliorated DHT-induced alterations of regulatory factors in human hair follicle dermal papilla cells (hHFDPCs) in a dose- and DP-dependent manner, as revealed by the normalization of several hair growth-stimulating or inhibitory factors. In vivo studies showed that AOS (DP2) extended anagen phase and thereby delayed catagen progression in mice. Furthermore, AOS (DP2) stimulated dorsal hair growth in mice by increasing hair length, density and thickness. Therefore, our findings indicated that AOS antagonized key factors involved in AGA pathogenesis, suggesting the potential application of AOS in prevention and treatment of AGA.